2021
DOI: 10.1038/s41598-021-87450-1
|View full text |Cite
|
Sign up to set email alerts
|

Seed-to-seed early-season cold resiliency in sorghum

Abstract: Early planted sorghum usually experiences cooler day/night temperatures, which may result in delayed growth, floral initiation, and infertile pollen, limiting productivity in high altitudes and temperate regions. Genetic variability for cold tolerance in sorghum has been evaluated by characterizing germination, emergence, vigor, and seedling growth under sub-optimal temperatures. However, the compounded effect of early season cold on plant growth and development and subsequent variability in potential grain yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
13
2
Order By: Relevance
“…Salinity reduces germination percentage, germination index, shoot length, root length, seedling vigor index and fresh and dry weight of shoot and root (Dehnavi et al 2020). Cold stress adversely affects the early growth and development of sorghum including emergence, seedling vigour, time to flowering, pollination, number of seeds in panicles and pollen production and general metabolism (Emendack et al 2021;Schaffasz et al 2019). All the above studies have revealed that the growth and yield of sorghum are severely affected by various abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity reduces germination percentage, germination index, shoot length, root length, seedling vigor index and fresh and dry weight of shoot and root (Dehnavi et al 2020). Cold stress adversely affects the early growth and development of sorghum including emergence, seedling vigour, time to flowering, pollination, number of seeds in panicles and pollen production and general metabolism (Emendack et al 2021;Schaffasz et al 2019). All the above studies have revealed that the growth and yield of sorghum are severely affected by various abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Tests showed a significantly greater variation and potential for cold tolerance in the msh1-derived epi-lines than those of their isogenic wildtype counterparts for seed germination and early plant growth features with no change in anthesis time. Successful early planting of sorghum, requiring cold tolerant seed germination, provides opportunity for crop expansion to new growing areas and efficient resource utilization (Emendack et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The term "cold tolerance or chilling tolerance" is used to describe the ability of sorghum to germinate, grow, and produce seed under conditions of low temperature but above freezing temperatures (Singh, 1985;Osuna-Ortega et al, 2003;Vera-Herna ́ndez et al, 2018;Emendack et al, 2021). Low temperature is one of the main abiotic stressors that affect plant growth and development and is a principal determinant of the geographical distribution of plants (Hurry et al, 2002;Mehrotra et al, 2020).…”
Section: Cold Tolerance: a Rare Trait In Sorghummentioning
confidence: 99%